Health Insurance Coverage Disruptions and Cancer Care and Outcomes: Systematic Review of Published Research - Yabroff, K Robin; Reeder-Hayes, Katherine; Zhao, Jingxuan; Halpern, Michael T; Lopez, Ana Maria; Bernal-Mizrachi, Leon; Collier, Anderson B; Neuner, Joan; Phillips, Jonathan; Blackstock, William; Patel, Manali (JNCI : Journal of the National Cancer Institute, 2020)
Lack of health insurance coverage is associated with poor access and receipt of cancer care and survival in the United States. Disruptions in coverage are common among low-income populations, but little is known about associations of disruptions with cancer care, including prevention, screening, and treatment, as well as outcomes of stage at diagnosis and survival. We conducted a systematic review of studies of health insurance coverage disruptions and cancer care and outcomes published between 1980 and 2019. We used the PubMed, EMBASE, Scopus, and CINAHL databases and identified 29 observational studies. Study characteristics and key findings were abstracted and synthesized qualitatively. Studies evaluated associations between coverage disruptions and prevention or screening (31.0%), treatment (13.8%), end-of-life care (10.3%), stage at diagnosis (44.8%), and survival (20.7%). Coverage disruptions ranged from 4.3% to 32.8% of patients age-eligible for breast, cervical, or colorectal cancer screening. Between 22.1% and 59.5% of patients with Medicaid gained coverage only at or after cancer diagnosis. Coverage disruptions were consistently statistically significantly associated with lower receipt of prevention, screening, and treatment. Among patients with cancer, those with Medicaid disruptions were statistically significantly more likely to have advanced stage (odds ratios = 1.2-3.8) and worse survival (hazard ratios = 1.28-2.43) than patients without disruptions. Health insurance coverage disruptions are common and adversely associated with receipt of cancer care and survival. Improved data infrastructure and quasi-experimental study designs will be important for evaluating the associations of federal and state policies on coverage disruptions and care and outcomes.